Real-time push middleware and mobile application for electric vehicle smart charging and aggregation. (1st January 2013) - Mal, Siddhartha; Gadh, Rajit
This paper presents a real-time push middleware and mobile application for data and multimedia content delivery to enable electric vehicle smart charging and aggregation. Intelligent aggregation and charge scheduling software can leverage the battery capacity of an EV to level peak loads by delaying or throttling charging during peak loads, 'valley fill' during off-peak times, and contribute to demand response and spinning reserves by sending electricity into the grid. EV users are updated on the status of their vehicle and may set their charge parameters via web or native mobile application. Facility and utility operators can monitor and control garage and microgrid status through a separate web or mobile application. The content to facilitate aggregated smart charging and monitoring may come from a variety of sources including web servers, ftp servers, Bluetooth or Zigbee or other protocol sensors, and local or remote databases. The middleware will accept content upload and database storage, securely provide content to outside entities, match content to user subscriptions, use user context including connection speed, device type, and location to deliver appropriately formatted content, and provide a reliable mechanism for push content delivery to a multitude of devices including mobile phones and tablet.